Re-imagining the future for desert Australia: designing an integrated pathway for enhancing liveability. (2017) - Race, Digby; Dockery, Alfred Michael; Havas, Lisa; Joyce, Catherine; Mathew, Supriya; Spandonide, Bruno
The desert regions of the world comprise about 25% of the world's land surface and are home to 500 million people, yet are often portrayed as extreme places with resident communities marginalised from mainstream development. Australia has a relatively vast desert region, covering about 70% of the continent and home to about 200, 000 people. As in most desert regions around the world, perceptions of hardship and isolation are enduring images with communities seen to be stoic yet in need of subsidies from the 'mainstream' economy. The multi-dimensional nature of the debate about the future of Australia's desert region often leaves policy makers with little overarching synthesis to guide public policy. This article draws together research on climate change, energy, housing and transport to provide a transdisciplinary analysis of how the desert region could become a highly liveable and prosperous area for existing and new residents.